2018
DOI: 10.1021/acsenergylett.8b01457
|View full text |Cite
|
Sign up to set email alerts
|

Gas Evolution in All-Solid-State Battery Cells

Abstract: The formation of gaseous side products in liquid electrolyte-based lithium-ion batteries has been intensively studied in recent years and identified as being one of the sources of degradation (an indication of electrolyte and electrode instabilities). Herein, we demonstrate, to our knowledge for the first time, that gassing can also arise in all-solid-state battery cells made of Ni-rich layered oxide cathode materials and thiophosphate-based solid electrolytes. Combining isotopic labeling, titration for quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(145 citation statements)
references
References 32 publications
9
134
0
2
Order By: Relevance
“…Resultsf rom DEMS conducted on aL i/LNO cell are depicted in Figure 5a-c and Figure S2, showingt he gas evolution over three cycles as af unctiono fx(Li)a nd time, respectively.F igure 5c is am agnified view of the 3rd charge/ discharge cycle. [37] No furtherO 2 evolution is detected during formation of the monoclinic phase, thus suggesting as table lattice structure. For NCM CAMs, it has been reported that CO 2 evolution is ar esult of electrolyte oxidation duet oo xygen release from the lattice,a mong others.…”
Section: Differential Electrochemical Mass Spectrometrymentioning
confidence: 94%
“…Resultsf rom DEMS conducted on aL i/LNO cell are depicted in Figure 5a-c and Figure S2, showingt he gas evolution over three cycles as af unctiono fx(Li)a nd time, respectively.F igure 5c is am agnified view of the 3rd charge/ discharge cycle. [37] No furtherO 2 evolution is detected during formation of the monoclinic phase, thus suggesting as table lattice structure. For NCM CAMs, it has been reported that CO 2 evolution is ar esult of electrolyte oxidation duet oo xygen release from the lattice,a mong others.…”
Section: Differential Electrochemical Mass Spectrometrymentioning
confidence: 94%
“…The oxygen release from various NCMs was further studied by Jung et al, [91,219,220] clearly showing enhanced O 2 evolution with increasing Ni content. [227] For Li-rich layered oxides, the O 2 evolution usually occurs at high potentials. [213] We also note that O 2 evolution during both charging and discharging has been confirmed recently by DEMS measurements conducted on all-solid-state battery cells.…”
Section: In Situ Gas Analyticsmentioning
confidence: 99%
“…[213] We also note that O 2 evolution during both charging and discharging has been confirmed recently by DEMS measurements conducted on all-solid-state battery cells. [227] For Li-rich layered oxides, the O 2 evolution usually occurs at high potentials. [101,219,220] During initial high-voltage charging up to 4.5-4.6 V vs Li + /Li of HE-NCM CAMs, Li 2 MnO 3 -like domains are supposed to be activated by extraction of Li and O atoms from the lattice.…”
Section: In Situ Gas Analyticsmentioning
confidence: 99%
“…Copyright 2018, American Chemical Society. g,h) Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Recent Progress In Electrode Materialsmentioning
confidence: 99%